Social Portrait of a Student of a Non-State Higher Education Institution of St Petersburg (on the Example of AN НЕО “University associated with IA EAEC”) - N. P. Kirsanova; V. A. Glukhikh; A. S. Gonashvili; A. E. Geger (Дискурс, 2024)
Introduction. Article is the result of a case analysis to study the satisfaction of students of   the AN НЕО “University associated with IA EAEC” with the educational process as one of the   indicators of the quality of education. An analysis of various aspects of student satisfaction   with the activities of the university allows to identify problems in the organization of the   learning process and find the best ways to solve them using available resources. In addition,   determining the overall level of student satisfaction allows making managerial decisions   based on relevant information about the needs of students and the quality of educational   services provided. The purpose of the article is to analyze the degree of satisfaction of   students of AN НЕО “University associated with IA EAEC” with the educational process in   general and their career orientations. This formulation of the question will allow to identify   more accurately the problems and needs of students, as well as to develop   recommendations for improving the quality of the educational process itself.  Methodology and sources. The case-study method was chosen as the methodological   strategy. The main research method in the work is a survey.  Results and discussion. The results of sociological research conducted in the form of a   questionnaire survey are presented. The type of sampling is continuous. According to the   results of the survey, students demonstrate pragmatism and focus on results in the learning   process. Thus, 70.6 % stated that only intrinsic motivation helps them to study. In difficult   competitive conditions, students need to be sure that the profession they get in higher   education will be in demand, that their knowledge will be enough to compete effectively  with other graduates in the labor market. In these conditions, modern students are aimed   not so much at obtaining fundamental knowledge as at acquiring practical skills.  Conclusion. One of the main results of the analysis is the conclusion that the most painful   issues for students are the issues of internship and grant opportunities. The university   management should pay the most attention to these two aspects of satisfaction, i.e.,   internship places and grant opportunities.